THE USE OF PIE TECHNIQUE IN TEACHING WRITING SKILL - Putri Septa Riani; Farnia Sari (Universitas Tridinanti Palembang, 2020)
The aim of this study is to investigate differences of students’ writing skill in analytical exposition text between the eleventh grade students of SMAN 11 Palembang who are taught by using PIE Technique and those who are not. The population of this study is the eleventh grade students of SMAN 11 Palembang in academic year of 2019/2020 wih the total number of students is 515 comprising 12 classes. The sample consists of two groups, experimental and control groups for each group consists of 40 students with the total numbers of 80 students. In collecting the data, pretest, treatment and posttest are used to obtain the data. The results show that the result of paired sample t-test in experimental group showed that the t-obtained (11.902) was higher that t-table (1.684). The result of paired sample t-test in control group showed that the t-obtained (5.609) was higher than t-table (1.684). The result of independent t-obtained (10.718) was higher than t-table (1.664). The data used to analyze by using t-test find that there is a significant difference in writing skill between the students who are taught by using PIE Technique and those who are not.Keywords: PIE technique, teaching, writing skill,